2007
DOI: 10.1021/la701154w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of a Novel Class of Gemini Pyridinium Surfactants

Abstract: A novel class of gemini pyridinium surfactants with a four-methylene spacer group was synthesized, and their surface-active properties and interactions with polyacrylamide (PAM) were evaluated by surface tension, fluorescence, and viscosity measurements. A comparison between the gemini pyridinium surfactants and their corresponding monomers was also made. The cmc's of gemini pyridinium surfactants are much lower than those of the corresponding monomeric surfactants. The C20 value is about one order of magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 26 publications
(38 reference statements)
6
101
1
Order By: Relevance
“…Among the surfactants, Gemini surfactants especially attract scientists' attention [37,38,[46][47][48][49][50][51][52] It is also known that one of the most important processes leading to micellar effects on reactions is the solubilization of solutes in micellar phase [53]. In this study, both Mn(III) catalysts and substrate PNPP are less water-soluble, so the introduction of cationic surfactants benefit an increase in local concentration of catalyst and PNPP molecules in a small volume inside micelle aggregates.…”
Section: Impact Of Various Surfactant Micelles On the Catalytic Hydromentioning
confidence: 93%
“…Among the surfactants, Gemini surfactants especially attract scientists' attention [37,38,[46][47][48][49][50][51][52] It is also known that one of the most important processes leading to micellar effects on reactions is the solubilization of solutes in micellar phase [53]. In this study, both Mn(III) catalysts and substrate PNPP are less water-soluble, so the introduction of cationic surfactants benefit an increase in local concentration of catalyst and PNPP molecules in a small volume inside micelle aggregates.…”
Section: Impact Of Various Surfactant Micelles On the Catalytic Hydromentioning
confidence: 93%
“…The spectral data of one representative monocationic surfactant, 1-(4 0 -hexadecyloxy benzyl)-3-methyl imidazolium bromide [C 16 …”
Section: Spectral Datamentioning
confidence: 99%
“…Baltazar et al [9] first reported synthesis and evaluation of surface properties of some dicationic imidazolium-based surfactant. A novel class of pyridinium-based gemini surfactants have also been synthesized and evaluated for their surface properties [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Gemini amphiphiles are the class of compound with twin hydrophobic tails linked with hydrophilic head with or without spacer [10]. Gemini amphiphiles are more beneficial as compared to single tailed ionic amphiphiles, because of their high surface activity, low critical micelle concentration [11], better solubilizing ability and greater ability to form stable structures with globular proteins [12,13]. In the recent instance, the interaction of globular protein with single tailed and Gemini amphiphiles had been investigated by the different research groups [14][15][16][17].…”
Section: Introduction Bioactive Peptidesmentioning
confidence: 99%